(3bUjOI MGFjI aj GdRgOs - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s ((3Ydi Hf RjO Hf CMeO Hf CHj jMji s)
(3ChdgG (B:s
(3GdCeQ LO hgh ZjQ eRGM aGYed dfaSc UGdMkG jG UGM s
(3BNQgG (B:s
(3hBNQ GdehLhO efgG (B: (3cdG hdG HYSGcQ hOSGcQ hLMGad heYGbd hedGM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GfXQ GdcejJjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B86s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs